1997
DOI: 10.1124/mol.52.4.676
|View full text |Cite
|
Sign up to set email alerts
|

Residues at Positions 206 and 209 of the α1 Subunit of γ-Aminobutyric AcidAReceptors Influence Affinities for Benzodiazepine Binding Site Ligands

Abstract: Ligands of the benzodiazepine binding site allosterically modulate gamma-aminobutyric acidA receptors. Their binding pocket is made up of amino acid residues located on both alpha and gamma subunits. We transiently expressed wild-type alpha1beta2gamma2 and mutant GABAA receptors in human embryonic kidney 293 cells and determined their binding properties. Receptors containing the mutant alphaY209A showed approximately 40-fold decrease in affinity for [3H]Ro 15-1788 and diazepam, whereas zolpidem displayed no me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 32 publications
7
88
0
3
Order By: Relevance
“…The inferred arrangement of subunits around the channel pore is hypothetical, based on the findings that the GABAbinding site is located at intersubunit contacts between ␣ and ␤ subunits (17)(18)(19)(20)(21) and that homologous amino acid residues of ␣ and ␥ subunits form the benzodiazepine-binding pocket (22)(23)(24)(25)(26)(27)(28). The observation that assembly intermediates comprising ␣␥ or ␣␤ dimers displayed some benzodiazepine or agonist binding, respectively (29), supported conclusions drawn from the former mutation studies.…”
supporting
confidence: 53%
“…The inferred arrangement of subunits around the channel pore is hypothetical, based on the findings that the GABAbinding site is located at intersubunit contacts between ␣ and ␤ subunits (17)(18)(19)(20)(21) and that homologous amino acid residues of ␣ and ␥ subunits form the benzodiazepine-binding pocket (22)(23)(24)(25)(26)(27)(28). The observation that assembly intermediates comprising ␣␥ or ␣␤ dimers displayed some benzodiazepine or agonist binding, respectively (29), supported conclusions drawn from the former mutation studies.…”
supporting
confidence: 53%
“…4B), the pendant phenyl of flunitrazepam also participates in -stacking with ␣1His101, underscoring the importance of an aromatic residue at this position. Studies have shown that an aromatic ring at position 209 is crucial for maximal diazepam mediated modulation of GABA current as well as high-affinity zolpidem, flunitrazepam, and diazepam binding in ␣1␤2␥2 GABARs (Amin et al, 1997;Buhr et al, 1997b). In our dock, a potential hydrogen bond between ␣1Thr206 (loop C), and the nitro group (Fig.…”
Section: Determinants Of Zolpidem Binding In the Gabar ␥2 Subunit 43mentioning
confidence: 99%
“…For example, a1-His102 directly interacts with flunitrazepam and diazepam (Berezhnoy et al 2004 ;McKernan et al 1998 ;Tan et al 2007), while a1-Tyr160, a1-Tyr210 (Amin et al 1997) and c2-Phe77 (Buhr et al 1997a) form part of the aromatic-binding site for benzodiazepines. Residues a1-Thr206, a1-Glu209, a1-Tyr162, a1-Thr207, c2-Tyr58, c2-Ala79, c2-Met130 and c2-Thr142 contribute to benzodiazepine selectivity and efficacy Buhr et al 1997aBuhr et al , 1997bKucken et al 2000 ;Mihic et al 1994 ;Teissere & Czajkowski, 2001).…”
Section: Benzodiazepinesmentioning
confidence: 99%